The effectiveness of reproductive midwifery care with the flour albus approach: A Case Study of handling vaginal discharge in women of childbearing age - Marbun, Uliarta; Sari, Nur Safitri; Irnawati, Irnawati; Sari, Lili Purnama; Dahniar, Dahniar (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: Women of childbearing age have a higher risk of vaginal discharge than adolescents because of the frequent occurrence of pelvic inflammatory disease (PID). One of the symptoms of reproductive organ infections in women is vaginal discharge. Objective: This study aims to apply midwifery care to cases of vaginal discharge (flour albus). Methods: A descriptive method with a case study approach is used. Data was collected through primary data, including assessment and observation of the patient's health status, interviews to obtain subjective data, and direct examination for objective data. Secondary data was obtained through patient records, registered books in the KIA room, and literature studies. Result: The results showed that the symptoms of vaginal discharge in patients included thick white mucus, unpleasant odor, and itching in the genital area. The care provided uses red betel leaf water decoction as a treatment effort. After obstetric care was carried out from July 16 to 20, 2024, the results were obtained that the patient's vaginal discharge improved without signs of genetic infection. Conclusion: The success of this care is also marked by an increase in patients' understanding of good personal hygiene, how to properly clean the feminine area from front to back, and the effective use of red betel leaf boiled water. Thus, the management of obstetric care applied to this case of vaginal discharge is quite successful and practical, with a decoction of red betel leaves providing a positive effect in reducing the incidence of pathological vaginal discharge.